FINANCIAL REWARDS CLIMATE AND ITS IMPACT ON EMPLOYEE ATTITUDES TOWARDS JOB SATISFACTION IN THE RETAIL ORGANIZATIONS - Sajjad Nazir; Wang Qun; Muhammad Naseer Akhtar; Amina Shafi; Nadia Nazir (European Scientific Journal, ESJ, 2015)
Job satisfaction is an attitudinal variable that reflects how people feel about their jobs overall. All aspects of the particular job, good or bad, Positive or negative, are likely to contribute to the development of feelings of satisfaction or dissatisfaction. The endeavor of this research was to find out whether financial rewards have an influence on the attitudes and feeling of employees. A questionnaire was constructed, analyzed and managed a total of 172 employees in the retail organization. Thus 172 usable surveys were analyzed the attitudes of employees on different aspects of their job. Findings showed that financial rewards caused positive job satisfaction of employees and boosted their commitment and increase the output of the organization. However, a high level of employee dissatisfaction was recorded in employee compensation and the amount of work they perform and the amount of responsibilities they accept. The result of this study highlights the role of job satisfaction of employees' and responsibilities of organizations in the promotion of good quality practices of HRM in retail business, and offers a substitute alleyway for employees' satisfaction and performance.